Die Kommission zur Erforschung von Sammlungen archäologischer Funde und Unterlagen aus dem nordöstlichen Mitteleuropa (KAFU). Krieg und Zerstörung – Wiederherstellung, Rekonstruktion und Forschung. Die Arbeiten der Jahre 2001 bis 2019 - Voß, Hans-Ulrich (e-Forschungsberichte des DAI, 2020)
During the Second World War, museums and collections with long-standing traditions, including their associated research archives, were destroyed; surviving collections and archives were frequently scattered widely. Large parts of Poland, Lithuania and the Russian Federation were particularly affected. The “Commission for the Research of Collections of Archaeological Finds and Documents from Northeastern Central Europe“, founded in 2001 by the Museum für Vor- und Frühgeschichte of the Prussian Cultural Heritage Foundation (MVF of the SPK) in Berlin and the Roman-Germanic Commission of the German Archaeological Institute on the initiative of German and Polish scholars, has set itself the task of tracking down and identifying, cataloguing, publishing and integrating the remaining finds and archival materials into current r research projects on the early history of the southern Baltic region between the river Oder and the Curonian Spit.